1983
DOI: 10.1037/0022-006x.51.5.702
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral comparisons of children from abusive and distressed families.

Abstract: The abused child is often described as being difficult to manage and delayed in several areas of psychosocial development in comparison with normal children. Although recent studies have attended to the developmental consequences of abuse, little consensus has been reached regarding the extent and nature of behavior problems among these children. The present study investigated the problem behaviors of a group of school-aged abused children in comparison with a sample of nonabused children from a child welfare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(52 citation statements)
references
References 13 publications
4
47
1
Order By: Relevance
“…The impact of this on the ratings remains to be determined. Wolle and Mosk (1983), in a frequently cited study, found that physically abused children were rated by parents as significantly higher in both internalizing and externalizing problems and lower in social competence than a community sample of nonabused children. However, these investigators also found that the ratings for the abuse group, recruited from a child welfare agency, were not different from the ratings for a nonabused group recruited from the same agency and also experiencing substantial family distress.…”
Section: Discussionmentioning
confidence: 95%
“…The impact of this on the ratings remains to be determined. Wolle and Mosk (1983), in a frequently cited study, found that physically abused children were rated by parents as significantly higher in both internalizing and externalizing problems and lower in social competence than a community sample of nonabused children. However, these investigators also found that the ratings for the abuse group, recruited from a child welfare agency, were not different from the ratings for a nonabused group recruited from the same agency and also experiencing substantial family distress.…”
Section: Discussionmentioning
confidence: 95%
“…Still, existing work supports our expectations. Abused and neglected children have lower IQ scores (Rogeness, Amrung, Macedo, Harris, & Fischer, 1986;Sadeh, Hayden, McGuire, & Sach, 1994), are less oriented toward educational and vocational goals (Hjorth & Ostrov, 1982), and have poorer general academic performance (Eckenrode, Laird, & Doris, 1993;Gelles & Straus, 1990;Rogeness et al, 1986;Salzinger, Feldman, Hammer, & Rosario, 1991;Tarter, Hegedus, Winsten, & Alterman, 1984;Wolfe & Mosk, 1983). Victims of abuse and neglect also have lower educational attainment in early adulthood (Perez & Widom, 1994).…”
Section: Life Course Links Between Victimization and Socioeconomic Atmentioning
confidence: 95%
“…Research indicates that child maltreatment may have undesirable effects upon child development (Burgess & Conger, 1978;Egeland & Sroufe, 1981;Egeland, Sroufe, & Erikson, 1983;George & Main, 1979;Grusec & Goodnow, 1994;Smetana & Kelly, 1989;Wolfe & Mosk, 1983). Despite its importance in terms of child care, most studies on child maltreatment have involved only individuals who consulted at clinics or allied social agencies.…”
Section: Introductionmentioning
confidence: 94%